Development of Mathematics Adventure Educational Game on SPLDV Material to Improve Students' Mathematical Connection Ability - Soleha, Rizki Putri; Wulantina, Endah (Department of Mathematics Education Program IPI Garut, 2023)
Rendahnya kemampuan koneksi matematis siswa dalam pembelajaran, khususnya materi SPLDV menjadi pendorong dilakukannya penelitian ini. Alat bantu seperti media pembelajaran permainan edukatif sangat diperlukan untuk meningkatkan hubungan matematis. Penelitian ini bertujuan untuk menyediakan media pembelajaran yang valid, praktis, dan efektif untuk meningkatkan kemampuan koneksi matematis siswa dalam bentuk game edukasi Mathematics Adventure pada materi SPLDV. Jenis penelitian ini adalah penelitian pengembangan (Research and Development) model ADDIE yang terdiri dari lima tahapan yaitu, analysis , design, development, implementation, dan evaluation. Uji coba produk dilakukan pada siswa kelas VIII SMP Negeri 3 Batanghari. Instrumen pengumpulan data menggunakan validasi ahli, angket respon siswa, dan tes. Hasil penelitian menunjukkan game edukasi Mathematics Adventure sangat valid berdasarkan penilaian para ahli, respon siswa memenuhi standar sangat praktis dan hasil belajar efektif untuk meningkatkan kemampuan koneksi matematis siswa. The low level of students' mathematical connections in learning, particularly in SPLDV material, is the impetus for this research. Educational game learning media tools are necessary to enhance mathematical relationships. This study aims to provide legitimate, practicable, and effective learning media in the form of Mathematics Adventure educational game on SPLDV material to enhance students' mathematical connection abilities. This research follows the ADDIE model of Research and Development, consisting of five stages: analysis, design, development, implementation, and evaluation. The product was tested on the eighth-grade students of SMP Negeri 3 Batanghari. Data collection instruments included expert validation, student response questionnaires, and tests. The results indicated that the educational game Mathematics Adventure was highly valid based on expert assessment, student responses met practical standards, and learning outcomes were effective in improving students' mathematical connection abilities.